INVESTIGASI HIDRODINAMIKA ALIRAN PADA TRIMARAN PLANNING TERHADAP VARIASI BENTUK TUNNEL - Arya Gumelar Prasetyo (2022)
Trimaran is a ship that has three hulls consisting of a main hull and a side hull usually by the deck on the upper side and the tunnel on the lower side. This study aims to vary the tunnel while maintaining the main size. The ship model is the AMECRC 9 series model and controls the half-cylindrical, flat and trapezoidal tunnel section with the highest point of 0.145 m. Flow hydrodynamics investigation and calculation model using the Computational Fluid Dynamic (CFD) method with the help of ANSYS software. The hydrodynamic analysis of the three variations of the tunnel was carried out on the resistance components including total resistance, viscosity resistance and wave resistance with variations in speed, namely Fn 0.4; 0.6; 0.8; 1.0 and 1.2. From testing with CFD simulations, it can be said that the lowest average total drag coefficient (CT) is the variation of tunnel 2 at froude number 1.2 with a value of 0.004174. The lowest resistance is obtained at the highest speed. The higher speed will affect the stern trim of the ship, thereby reducing the drag on the hull area that is submerged by water.